Legal Protection for Medical Personnel Who Neglect Their Duties in Performing Medical Procedures Under Law No. 17 of 2023 on Health - Wulan, I Gusti Kencana; Rokhim, Abdul; Muhibbin, Moh. (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study examines the legal protection of medical personnel who commit negligence in medical procedures within the framework of Law Number 17 of 2023 concerning Kesehatan. Legal conflicts involving medical professionals often create destructive and counterproductive impacts on the overall health service system, making it essential to understand the balance between accountability and protection. The objective of this research is to analyze the types of legal sanctions applicable to negligent medical personnel, as well as the scope of legal protection granted to them under Indonesian health law. The research applies a normative legal approach, utilizing deductive and inductive reasoning, and employs both conceptual and statutory methods. Primary, secondary, and tertiary legal materials are used to support the analysis. The findings indicate that negligent medical personnel may be subject to administrative, civil, or criminal sanctions. Civil liability, especially when patient harm occurs, is prioritized through alternative dispute resolution mechanisms outside the court (Article 308 paragraph (1) of Law No. 17/2023). Criminal liability is applicable when medical personnel are proven to have engaged in unlawful conduct, but it requires a recommendation from a professional discipline panel appointed by the Minister of Health. Importantly, Article 273 paragraph (1) letter a affirms that medical personnel are entitled to legal protection provided they perform their duties in accordance with professional standards, service standards, operational procedures, medical ethics, and patient health needs. In conclusion, the law aims to establish legal certainty that ensures accountability while safeguarding medical personnel from unjust criminalization. This framework strengthens professional integrity, enhances patient protection, and fosters public trust in the healthcare system.